Assessing the influence of lactic acid fermentation on the biochemical indicators of plant substrates and substantiating the rational process duration - Bal-Prylypko, Larysa; Nikolaenko, Mykola; Serdyuk, Marina; Bandura, Valentyna; Danylenko, Svitlana; Sydorenko, Olena; Kurbatova, Inna; Nesterenko, Natalia (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the lactic acid fermentation process involving plant substrates of various natures (spelt, flax seeds, kelp, oyster mushrooms) with the participation of Lactiplantibacillus plantarum. The task addressed relates to the insufficient certainty of the patterns in biochemical transformations in plant substrates of various natures in the lactic acid fermentation process. This complicates their targeted selection and use as fermented ingredients in food products. Fermentation was carried out at a temperature of 32 ± 2°C for 24 hours with sampling every 6 hours. It was established that the pH dynamics have a phase character: the most intensive decrease occurs in the interval of 0–6 hours. The total pH decrease was 33.0% for spelt, 28.5% for oyster mushrooms, 20.2% for flax, and 12.2% for kelp. The average rate of pH decrease over 24 hours was from –0.088 units/h (spelt) to –0.034 units/h (kelp). An increase in titrated acidity was found in all substrates, the most intense for spelt and oyster mushrooms: 9.35 and 9.5 times, respectively, with average rates of 0.042 and 0.040 g/100 g/h. For flax and kelp, the increase was lower – 0.48 and 0.28 g/100 g, respectively. A strong inverse correlation was found between pH and titrated acidity (r = –0.98 ± 0.03). The decrease in soluble carbohydrates was 46.2% in oyster mushrooms and 42.3% in spelt, while in kelp and flax – 6.7% and 13.8%. The content of soluble protein increased by 58% in kelp, 50% in flax, 43% in spelt and 33% in oyster mushrooms in the absence of significant changes in total protein. It was found that after 18 hours of fermentation, the rate of change of all indicators is significantly reduced. It was substantiated that the rational duration of fermentation is 18 hours, which enables a balanced acid profile and effective transformation of the carbohydrate-protein complex without excessive acidification